PERANCANGAN SISTEM KEPEGAWAIAN (HUMAN RESOURCE MANAGEMENT) BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER DI RUMAH SAKIT ADVENT BANDAR LAMPUNG - Joseph Hamonangan (TeIKa, 2021)
Bandar Lampung Adventist Hospital (RSABL) is a professional health care institution that has a human resources management system that uses Ms. Excel. (Human Resource Department) HRD will process data for each existing employee using data processing media (software) to create documentation regarding attendance to salary analysis based on managed attendance. Programming technology and databases as storage media can be useful in helping classify information data. The development of the system used in this research is the waterfall. This method consists of requirements gathering, analysis, system design, implementation, testing, and maintenance. This system is designed using the Codeigniter framework. The results of the trial of the Human Resource Management system can manage employee data, manage absent data, submit leave requests and salary data at RSABL properly.